Technical Considerations and Pitfalls of BASILICA: Bioprosthetic or Native Aortic Scallop Intentional Laceration to Prevent Iatrogenic Coronary Artery Obstruction. Issue 3 (3rd May 2020) - Komatsu, Ikki; Wijeysandera, Harindra; Radharkrisnan, Sam; Whisenant, Brian; Simonato, Matheus; Chen, Albert; Mackensen, G. Burkhard; Reisman, Mark; Spies, Christian; Goel, Kashish; Abdel-Wahab, Mohamed; Dvir, Danny
ABSTRACT: Coronary obstruction is a major complication of transcatheter aortic valve replacement (TAVR). Rapid and growing demand for TAVR procedures is accompanied by interest in techniques that may prevent this life-threatening adverse event. BASILICA (Bioprosthetic or Native Aortic Scallop Intentional Laceration to Prevent Iatrogenic Coronary Artery Obstruction) is a transcatheter technique that may effectively prevent coronary obstruction. Formal proctorship and assistance by operators already experienced with the performance of BASILICA is beneficial to ensure good clinical outcomes. This review describes the BASILICA procedure and outlines selected technical considerations and pitfalls. Abbreviations: TAVR: transcatheter aortic valve replacement; BASILICA: Bioprosthetic or Native Aortic Scallop Intentional Laceration to Prevent Iatrogenic coronary Artery Obstruction; THV: transcatheter heart valve; VTC: virtual valve to coronary distance; ViV: valve-in-valve; VIVID: valve in valve international data.